Transition Zone in Total Colonic Aganglionosis and Colorectal Hirschsprung's Disease Shows a Similar Trend of Mucosal Innervation: Image Processing and Analysis Study. (April 2020) - Cordeiro-Rudnisky, Fernanda; Ahn, Sangtae; Sheuka, Natallia; Whyte, Christine; Boguniewicz, Ann; Fan, Rong; Lin, Jingmei; Jennings, Timothy A; Lee, Hwajeong
The aganglionic segment of bowel in Hirschsprung's disease (HD) varies in length. It is not clear whether total colonic aganglionosis (TCA) merely represents a long form of HD or a different phenotype of the disease. Animal model studies suggest that TCA may have a longer transition zone (TZ) than conventional colorectal HD. We compared mucosal innervation of TZ in 2 TCA cases and 10 conventional colorectal HD cases by quantifying calretinin-positive mucosal nerve fibers using image processing and analysis. One TCA was associated with esophageal atresia-tracheoesophageal fistula, the other with trisomy 21. The gradients of calretinin-stained pixel count increase per distance from the beginning of TZ (slope) for TCA were not significantly different from those for the conventional HD group. Given this observation, it is speculated that the length of TZ in TCA may fall within the range of and may not be much longer than conventional colorectal HD.